A framework for a net environmental benefit analysis based comparative assessment of decommissioning options for anthropogenic subsea structures: A North Sea case study - Nicolette, Joseph P.; Nelson, Nicholas A.; Rockel, Michael K.; Rockel, Mark L.; Testoff, Alex N.; Johnson, Larry L.; Williamson, Laura D.; Todd, Victoria L. G. (Frontiers in Marine Science, 2023)
Taxpayers and operators worldwide have significant current liabilities associated with decommissioning of offshore Oil & Gas (O&G) assets. Consequently, decommissioning is at the forefront of industrial, governmental, and non-governmental agendas. Decommissioning is a highly complex activity with health, safety, environmental, social, economic, and technical implications. Increasing scientific evidence supports that manmade subsea structures create hard, artificial reef habitats that provide ecological and social benefits to society. Given the significant uncertainty regarding how subsea structures should be retired at the end of their operational lifetimes, it is necessary for governments, taxpayers, and operators to understand the risks and benefits associated with potential decommissioning options. Currently, the North Sea decommissioning process is based on the policies and direction of the Oslo and Paris Convention’s (OSPAR) Decision 98/3 and follow comparative assessment (CA) multiple-criteria decision analysis (MCDA) guidelines to determine the best overall strategy for decommissioning subsea structures; however, CA MCDA processes can be biased, ambiguous, difficult to use, interpret, and replicate, and limited in their consideration of multigenerational benefits. Consequently, to assist decision-makers in understanding and evaluating options and associated benefits for decommissioning subsea structures, this study adapted the net environmental benefit analysis (NEBA) framework to supplement and strengthen the CA process for evaluating decommissioning options for offshore O&G facilities. The net environmental benefit analysis based comparative assessment (NEBA-CA) framework is presented that addresses the growing need for a practical, quantitative, scientifically robust, defendable, and transparent MCDA approach to determine optimized decommissioning strategies for subsea assets. Increased transparency in CAs will provide an additional layer of credibility with regulators and society. The approach is data driven and a desktop analysis mainly relying on existing data. Using a North Sea case study, this work demonstrates the ability of NEBA-CA to resolve inherent complexity in comparing decommissioning options, thereby supporting operators in working with regulators to decommission assets in a way that maximizes ecosystem service benefits to society while managing site-related risks and costs. The NEBA-CA framework supplements and strengthens the standard CA process by 1) incorporating quantified metrics including multigenerational ecosystem service benefits and risks, 2) excluding front ranking (scoring) or weighting of metrics, and 3) providing consistent graphical displays to support visual differentiation of options and metrics.